Peculiarities of Applying Investment Tax Deductions - N. A. Bondareva (Учёт. Анализ. Аудит, 2020)
The imposition of economic sanctions on the Russian Federation by the countries of Europe and the United States, the introduction of import substitution required the modernization of production, the development of new technologies and the growth of labor productivity. To achieve these goals, significant investments are required in the economy, in particular, attracting investments from individuals and legal entities. The paper describes tax aspects of investing. The methodological basis of the study is tax legislation and local legislative acts of the regions. The analysis of investment activity of individuals shows the state of fixed assets of companies and the dynamics of investment activity for some types of economic activity in conformity with the current state policy to restore fixed capital. The author revealed that the number of individual investors and the amount of investment deductions received by them have increased more than twice, but the investments volume in the segment of large and medium-sized businesses continued to decrease. There was tension in the formation of regional budgets. To intensify the investment activity of companies, the author recommends to extend the application of the investment tax deduction to lowincome companies and reformat regional budgets for the least loss of funds when they are temporary diverted. The study may be of interest to state and regional authorities when developing indicators for the application of investment tax deductions.